Analisa Perawatan Mesin Penyuir Daging Sapi - Ichlas Nur; Rivanol Chadry; Wafi Aulia Alfin (Politeknik Negeri Padang, 2017)
An analysis has been carried out to treat the meat grinder machine. The care of the meat grinder machine is important to help the production process of rendang suir craftsmen. Meat grinder machine consists of several components, namely the engine, electric motor, pulleys, V-belts, reservoirs, and spindle shaft. With the components above, this meat grinder machine is expected to work optimally with satisfactory results. The meat grinder machine treatment consists of repairing, repairing, total care. Canceled maintenance consists of recovery, lubrication, and periodic checks. Repair treatments include maintenance of the blade, bearing care, pulley care and belt. While total maintenance is carried out after the engine has been running long enough. The result of the treatment that has been done is a machine that can be run properly which can produce a maximum of 30 kg / hour